Challenges in Implementing the Scientific Paradigm at UIN Imam Bonjol Padang: A Case Study of the Constitutional Law Study Program - Muhammad Taufik; Aidil Aulya; Fauzi Yati; Desip Trinanda (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
This study examines the challenges in implementing the scientific paradigm of Universitas Islam Negeri Imam Bonjol Padang (UIN IB Padang) in the Constitutional Law Study Program (Siyāsah Shar’iyyah). A qualitative approach was employed, utilizing interviews, observations, and documentation for data collection. The findings reveal that UIN IB Padang adopts an interaction-dialogical paradigm, which has been implemented in the Constitutional Law Study Program (Siyāsah Shar’iyyah), as reflected in the curriculum structure. However, this implementation remains formalistic, as lecturers have not fully applied the paradigm in teaching. This is due to the lecturers' lack of updated knowledge regarding the interaction-dialogical paradigm and the absence of specific teaching guidelines provided by UIN IB Padang. Additionally, the development of the Constitutional Law Study Program (Siyāsah Shar’iyyah) faces challenges within the context of Indonesian Constitutional Law. This study recommends that UIN IB Padang develop a guideline for implementing the interaction-dialogical paradigm and establish a dedicated institution to support its application and development.